HUBUNGAN KESELAMATAN DAN KESEHATAN KERJA (K3) DENGAN PRODUKTIVITAS KERJA PETUGAS PUSKESMAS MANDIRANCAN KABUPATEN KUNINGAN - Husaini Husaini; Maula Ismail Mohammad; Elfi Elfi; Totok Subianto (J-KESMAS: Jurnal Kesehatan Masyarakat, 2026)
Human resources play a vital role in enhancing the effectiveness of healthcare services, particularly in response to low national productivity and the high rate of occupational accidents in West Java. Given that community health center (Puskesmas) staff are directly exposed to risks such as infectious diseases, chemical substances, and high workloads, the implementation of Occupational Health and Safety (OHS) is a crucial instrument for protecting personnel while ensuring the quality of service. Based on preliminary observations at Mandirancan Public Health Center, there were indications that OHS procedures were not yet optimal and occupational accidents still frequently occurred; thus, this study was conducted to analyze the correlation between OHS variables and employee work productivity. Using a quantitative analytical approach with a cross-sectional design, this study involved the entire population of 45 workers at Mandirancan Public Health Center through a total sampling technique. Data gathered via questionnaires and document reviews were analyzed using the chi-square test, which revealed that the majority of respondents (60.0%) had implemented OHS well and possessed high work productivity (57.8%). Statistically, a significant relationship was found between OHS and work productivity (p-value = 0.036), indicating that within the scope of this research, adequate safety standards contribute significantly to the work performance of staff at Mandirancan Public Health Center.